The Relationship Between Mother's Knowledge about Booster Immunization with Complete Basic Immunization in the Working Area of Bojong Rawa Lumbu Health Center - Mariyani Mariyani (STIKep PPNI Jawa Barat, 2023)
Aims: According to Ministry of Health figures, BCG vaccine coverage was 93.8% of the target number of 4,461,341 newborns, DPT 1 was 69.6%, Polio 1 was 76.6%, Polio 4 was 92.4%, and measles was 91%. The status of complete basic immunization completeness in children in the province of Java The West in 2018 was 57.9%, slightly lower than Riskesdas 2013, which is 59.2%, while the average value of completeness immunization in Indonesia is 59.2%. Method: In this study, 73 people were asked to take part. Total selection was the method that was used. The chi-square test was used to look at a descriptive association and a cross-sectional method. Results: Complete basic immunization was done by respondents at the Bojong Rawa Lumbu Health Center. Univariate selection was done, and knowledge is not just gained from having a better level of schooling. You can also get information from the mass media, from personal and other people, and from health workers who take part. Conclusion: The level of basic immunization completion at the Bojong Rawa Health Center is correlated with the mother's level of knowledge regarding booster immunization.